Quantitative Proteomic Analysis of the Response of Probiotic Putative Lactococcus lactis NCDO 2118 Strain to Different Oxygen Availability Under Temperature Variation - Marques Da Silva, Wanderson; Oliveira, Leticia Castro; Soares, Siomar Castro; Sousa, Cassiana Severiano; Tavares, Guilherme Campos; Resende, Cristiana Perdigão; Pereira, Felipe Luis; Ghosh, Preetam; Figueiredo, Henrique; Azevedo, Vasco (Frontiers in Microbiology, 2019)
Lactococcus lactis is a gram positive facultative anaerobe widely used in the dairy industry and human health. L. lactis subsp. lactis NCDO 2118 is a strain that exhibits anti-inflammatory and immunomodulatory properties. In this study, we applied a label-free shotgun proteomic approach to characterize and quantify the NCDO 2118 proteome in response to variations of temperature and oxygen bioavailability, which constitute the environmental conditions found by this bacterium during its passage through the host gastro-intestinal tract and in other industrial processes. From this proteomic analysis, a total of 1,284 non-redundant proteins of NCDO 2118 were characterized, which correspond to approximately 54% of its predicted proteome. Comparative proteomic analysis identified 149 and 136 proteins in anaerobic (30 ºC and 37 ºC) and non-aerated (30 ºC and 37 ºC) conditions, respectively. Our label-free proteomic analysis quantified a total of 1,239 proteins amongst which 161 proteins were statistically differentially expressed. Main differences were observed in cellular metabolism, stress response, transcription and proteins associated to cell wall. In addition, we identified six strain-specific proteins of NCDO 2118. Altogether, the results obtained in our study will help to improve the understanding about the factors related to both physiology and adaptive processes of L. lactis NCDO 2118 under changing environmental conditions.